Applying audit procedures into auditing tangible fixed asset items in Financial Statement performed by Ernst & Young Vietnam Limited Company - Dao, Quoc Hieu (H. : ĐHQGHN, 2020)
The thesis provides the theoretical basics of auditing tangible fixed assets section in the financial statements and from that analyzes the actual process of the audit this section performing by E&Y Vietnam. Through practical approach of audit process at the company, thesis points out some weaknesses and solutions, reasonable recommendations to improve the process of auditing the tangible fixed assets section perform by this company.